Assessing ChatGPT’s Information Quality Through the Lens of User Information Satisfaction and Information Quality Theory in Higher Education: A Theoretical Framework - Chung-Jen Fu; Andri Dayarana K. Silalahi; I-Tung Shih; Do Thi Thanh Phuong; Ixora Javanisa Eunike; Shinetsetseg Jargalsaikhan (Human Behavior and Emerging Technologies)
Incorporating AI tools like ChatGPT into higher education has been beneficial, yet the extent of user satisfaction with the quality of information provided by these tools, known as user information satisfaction (UIS) and information quality (IQ) theory, remains underexplored. This study introduces a UIS model specifically designed for ChatGPT’s application in the educational sector based on multidimensions of IQ theory. Drawing from established UIS and IQ theory, we crafted a model centered around seven essential factors that influence the effective use of ChatGPT, aiming to guide educators and learners in overcoming common challenges such as plagiarism and ensuring the ethical use of AI. Data was collected from Indonesian university participants (N=508) and analyzed using structural equation modeling with Smart-PLS 4.0. The results reveal that completeness, precision, timeliness, convenience, and information format are the most influential factors driving user satisfaction with ChatGPT. Interestingly, our research indicated that the accuracy and reliability of the information, typically deemed paramount, were not the primary concerns in the academic use of ChatGPT. Our findings recommend a cautious approach to integrating ChatGPT in higher education. We advocate for strategic use that recognizes its innovative potential while acknowledging its limitations, ensuring responsible and effective application in educational contexts. This balanced perspective is crucial for integrating AI tools into the academic fabric without compromising educational integrity or quality.